The promise of progress the life and work of Lewis Henry Morgan - Moses, Daniel Noah (University of Missouri Press, 2009)
"A detailed presentation of Lewis Henry Morgan's life from his early work with the Iroquois to his defense of American capitalism to his strange posthumous career among international leftists up to Morgan's influence among today's environmentalists, anarchists, feminists, and other social visionaries"--Provided by publisher.